Comorbidities in Patients before Surgical Myocardial Revascularization: Current State of the Problem. Part IІ - Olena K. Gogayeva; Alina Yu. Lebid; Dmytro A. Tymoshenko (Ukrainian Journal of Cardiovascular Surgery, 2022)
The first part of the article was dedicated to the problem of comorbidities in cardiac surgery patients with coronary artery disease (CAD), considered modern literary sources discussing endocrinopathies, connective tissue diseases, COVID-19-associated autoimmune processes, chronic kidney disease and diseases of the gastrointestinal tract.The aim. To continue the analysis of current literature data on comorbidities in patients hospitalized for surgical myocardial revascularization.Results. When assessing the preoperative status of a cardiac surgery patient with CAD, not only their cardiological status and the percentage of stenotic lesion of the coronary arteries are important, but also the presence of concomitant diseases and the degree of their compensation. According to the modern literary sources, 4-20.5% of patients undergoing coronary artery bypass grafting (CABG) have chronic pulmonary disease (COPD). In order to avoid bronchopulmonary complications in the postoperative period, high-quality preoperative diagnosis based on spirometric research is important. When verifying COPD, even of a moderate degree, a course of preventive therapy is required, and in the case of a severe course of COPD with a forced expiratory volume <50%, the involvement of a pulmonologist is necessary. Hemodynamically marked stenoses of brachiocephalic arteries are found in 6-12% of patients before CABG. According to European recommendations, ultrasound screening of carotid arteries is indicated for patients ≥70 years of age with multivessel lesions of the coronary arteries and a history of neurological disorders <6 months before planned cardiac surgery. Dementia is diagnosed in 9.6-20% of patients before CABG and is characterized by a higher rate of mortality and postoperative complications. It was established that the result of the cognitive function assessment using the Mini-Mental State Examination (MMSE) scale <24 is an independent risk factor for in-hospital mortality and postoperative delirium. Concomitant disease of peripheral arteries is diagnosed in 6.1-20.4% of patients before CABG and negatively affects both immediate and long-term results of myocardial revascularization.Conclusions. Timely verification and compensation of comorbidities is an important point in the perioperative management of cardiac surgery patients with CAD. The systemic nature of the atherosclerotic process leads to multifocal stenotic lesions of the arterial system, which requires from the heart team not only to determine the priority of surgical interventions, but also to choose the optimal method of myocardial revascularization, taking into account comorbidities.